A graphite polyimide composite coating for titanium alloy fasteners and a method of making the same
Patent Information
- Application Number
- CN202611166513.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]另一方面,紧固件通常具有螺纹、圆柱面、过渡圆角等复杂结构特征,常规静态喷涂工艺难以实现复杂表面的均匀覆盖,易出现螺纹根部漏喷、局部堆积及涂层厚度不均等问题,从而影响涂层结合稳定性与高温服役可靠性
(1)、本发明构建了一种适用于钛合金紧固件表面的石墨/聚酰亚胺复合高温功能涂层。其中,聚酰亚胺树脂或聚酰亚胺前驱体作为成膜基体,能够提供优异的耐热性、成膜性及界面稳定性;石墨作为层状固体润滑相,可在摩擦过程中形成低剪切转移膜,降低界面剪切阻力。二者协同作用,使所得复合涂层兼具良好的高温稳定性、减摩抗磨性能及界面附着稳定性。实验结果表明,该复合涂层在室温条件下摩擦系数可低至0.2,在350℃条件下摩擦系数仍保持在0.2以下。
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fastener surface protection technology, specifically relating to a graphite polyimide composite coating for titanium alloy fasteners and its preparation method. Background Technology
[0002] Titanium alloy fasteners can typically operate at around 350°C for extended periods, but the relatively insufficient temperature resistance of their surface protective and lubricating coatings is a key factor limiting their reliability in high-temperature applications. While existing molybdenum disulfide-based solid lubricating coatings, widely used in titanium alloy fasteners, offer good friction reduction and anti-adhesion properties, they are prone to oxidation failure in air. Their long-term stable operating temperature is typically only around 220°C, and their lubrication and protective performance significantly degrades at higher temperatures, making it difficult to meet the requirements for 350°C high-temperature service. Therefore, developing a novel fastener surface coating system suitable for 350°C high-temperature environments is of great significance.
[0003] On the other hand, fasteners typically have complex structural features such as threads, cylindrical surfaces, and transition fillets. Conventional static spraying processes struggle to achieve uniform coverage of these complex surfaces, often resulting in issues like missed areas at the thread roots, localized build-up, and uneven coating thickness. This negatively impacts coating adhesion stability and high-temperature service reliability. Therefore, it is necessary to develop a spraying deposition process adapted to the complex structure of fasteners to achieve uniform and stable coating deposition on their surfaces. Summary of the Invention
[0004] The purpose of this invention is to provide a graphite-polyimide composite coating for titanium alloy fasteners and its preparation method, so as to achieve uniform and stable deposition of the composite coating on the surface of complex fasteners and improve the service reliability and surface protection capability of titanium alloy fasteners in high-temperature environments.
[0005] The above-mentioned objectives of the present invention are mainly achieved through the following technical solutions: A method for preparing a graphite-polyimide composite coating for titanium alloy fasteners includes the following steps: (1) Mix and disperse graphite powder with diluent to obtain graphite dispersion; (2) Add polyimide resin or polyimide precursor to graphite dispersion, then add dispersant, and stir to mix to obtain graphite / polyimide composite lubricating coating slurry; (3) Mix and stir deionized water, anhydrous ethanol and silane coupling agent to obtain intermediate layer slurry; (4) Apply the intermediate layer slurry to the surface of the fastener and pre-bake it; (5) Coat the graphite / polyimide composite lubricating coating slurry obtained in step (2) and cure it to obtain the graphite-polyimide composite coating.
[0006] In step (3), the volume ratio of deionized water, anhydrous ethanol and silane coupling agent is 1:2.5:1 to 1:3:1. Stirring is carried out under water bath heating conditions, with a heating temperature of 48 to 52°C and a time of 1 to 1.2 hours.
[0007] In step (4), before coating, the fasteners are degreased, cleaned, and dried to remove surface contaminants.
[0008] In step (4), the pre-baking temperature is 60℃~80℃ and the time is 5min~20min.
[0009] In step (5), the graphite / polyimide composite lubricating coating slurry is applied by spraying. After spraying, it is pre-baked. The spraying and pre-baking are repeated 2 to 4 times to complete the coating.
[0010] A rotary spraying method is used, in which the fastener rotates around its own axis during the spraying process.
[0011] In step (5), the curing method is step curing, specifically as follows: first, cure at 140~145℃ for 0.5~1h, then cure at 200~210℃ for 0.5~1h, and finally cure at 300~310℃ for 0.5~1h.
[0012] The diluent is N-N dimethylformamide, and the volume ratio of N-N dimethylformamide to polyimide resin or polyimide precursor is 1:1 to 1:1.1.
[0013] The mass of the polyimide resin or polyimide precursor is 65wt% to 75wt% of the total mass of the graphite polyimide composite coating, and the mass of the graphite powder is 25wt% to 35wt% of the total mass of the graphite polyimide composite coating.
[0014] The dispersant is polyvinylpyrrolidone, and the mass of the dispersant is 5% to 10% of the mass of the graphite powder. The graphite powder is flake graphite with a particle size ≤11μm.
[0015] A graphite-polyimide composite coating for titanium alloy fasteners is prepared using the above-described preparation method.
[0016] Compared with the prior art, the present invention has at least the following beneficial effects: (1) This invention constructs a graphite / polyimide composite high-temperature functional coating suitable for the surface of titanium alloy fasteners. The polyimide resin or polyimide precursor serves as the film-forming matrix, providing excellent heat resistance, film-forming properties, and interfacial stability. Graphite, as a layered solid lubricating phase, can form a low-shear transfer film during friction, reducing interfacial shear resistance. The synergistic effect of these two components results in a composite coating that possesses good high-temperature stability, friction-reducing and wear-resistant properties, and interfacial adhesion stability. Experimental results show that the coefficient of friction of this composite coating can be as low as 0.2 at room temperature, and remains below 0.2 even at 350℃.
[0017] (2) The present invention uses polyimide resin as the main matrix and combines it with a high-temperature stable graphite lubricating phase, which can significantly improve the heat resistance and high-temperature service capability of the coating, so that it can match the service requirements of 350℃ titanium alloy fasteners, thereby expanding the application range of titanium alloy fasteners.
[0018] (3) In this embodiment of the invention, a deposition process combining rotary spraying and multiple thin-layer spraying is preferably used to uniformly deposit the graphite / polyimide composite coating on the complex surface of the fastener. During the spraying process, the fastener rotates around its own axis, allowing the sprayed droplets to cover complex areas such as the crest, flank, and root of the thread, thereby improving the uniformity of coverage of the complex thread structure. At the same time, the multiple thin-layer spraying process can reduce the risk of sagging, accumulation, and local cracking caused by a single thick spraying. Compared with the traditional static spraying method, this invention can effectively reduce problems such as missed spraying at the root of the thread, uneven local thickness, and surface defects, and improve the deposition consistency and coating stability of complex structure surfaces. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the spraying method for the graphite / polyimide composite lubricating coating for titanium alloy fasteners of the present invention; Figure 2 The coefficient of friction of the graphite / polyimide composite lubricating coating prepared in Example 1 of this invention at 350°C. Detailed Implementation
[0020] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments: This invention relates to a graphite / polyimide composite lubricating coating for titanium alloy fasteners, comprising graphite powder, polyimide resin or polyimide precursor, diluent and dispersant; The diluent is N-N dimethylformamide, with a volume ratio of 1:1 to 1:1.1 with the polyimide resin, which decomposes and volatilizes during the high-temperature curing process; The polyimide resin accounts for 65wt% to 75wt% of the total solid components of the composite lubricating coating. The polyimide resin or polyimide precursor is cured from a polyimide solution with a solid content of 20%. Graphite powder accounts for 25 wt% to 35 wt% of the total solid components of the composite lubricating coating; The dispersant is polyvinylpyrrolidone, and the mass of the dispersant is 5% to 10% of the mass of the graphite powder. It decomposes and volatilizes during the high-temperature curing process.
[0021] Preferably, the graphite powder is flake graphite with a particle size ≤11 μm.
[0022] The present invention also relates to the application of the aforementioned graphite / polyimide composite lubricating coating for titanium alloy fasteners, wherein the composite lubricating coating is applied to the surface of the fastener by spraying.
[0023] A method for preparing a graphite-polyimide composite coating for titanium alloy fasteners includes the following steps: Step 1: Preparation of composite slurry First, graphite powder is added to N,N-dimethylformamide and pre-dispersed by mechanical stirring / ultrasonic dispersion to obtain a graphite dispersion. Subsequently, polyimide resin or polyimide precursor is added to the graphite dispersion, followed by the addition of a dispersant. The mixture is then stirred and mixed to obtain a graphite / polyimide composite lubricating coating slurry. The dispersant is used to improve the dispersion uniformity and interfacial bonding state of graphite in the polyimide system.
[0024] Step 2: Preparation of intermediate layer slurry Deionized water, anhydrous ethanol, and KH550 silane coupling agent are mixed evenly in a volume ratio of 1:2.5:1 to 1:3:1, and then placed in a water bath at 48 to 52°C and stirred for 1 to 1.2 hours to obtain the intermediate layer slurry. Step 3: Matrix Pretreatment The substrate of fastener sample 2 was degreased, cleaned, and dried to remove surface contaminants; Step 4: Rotary spraying like Figure 1 As shown, the fastener sample 2 is placed on the rotary spraying table 3, and the intermediate layer slurry is sprayed onto the surface of the fastener sample 2 after step 3 using a pneumatic spray gun 1. The fastener sample 2 rotates around its own axis during the spraying process to improve the uniformity of the intermediate layer coverage in the threaded area, cylindrical surface and transition area.
[0025] Step 5: Pre-baking After the intermediate layer slurry is sprayed, the fasteners are pre-baked at 60℃~80℃ for 5min~20min to remove some of the solvent and to initially stabilize the coating.
[0026] Step 6: Multiple thin-spray composite coating The graphite / polyimide composite slurry obtained in step 1 is sprayed onto the surface of the fastener treated in step 5. During the spraying process, the fastener rotates around its own axis. After spraying, it is pre-baked. The spraying and pre-baking operations are repeated 2 to 4 times. The composite lubricating coating is deposited layer by layer by multiple thin sprays to reduce the risk of local sagging and thick coating accumulation.
[0027] Step 7: Heat treatment and curing The fasteners are heat-treated and cured in a stepwise manner to cure the polyimide resin or to induce an imidization reaction in the polyimide precursor, ultimately forming a graphite / polyimide composite lubricating coating on the fastener surface.
[0028] Preferably, during the spraying process, the spraying distance between the pneumatic spray gun 1 and the fastener sample 2 is 15 cm to 20 cm.
[0029] Preferably, during the spraying process, the angle between the spray gun axis of the pneumatic spray gun 1 and the axis of the fastener sample 2 is 30° to 90°.
[0030] Preferably, the thickness of the graphite / polyimide composite lubricating coating is 20–35 μm.
[0031] Preferably, the stepped curing process is as follows: first, curing at 140~145℃ for 0.5~1h, then curing at 200~210℃ for 0.5~1h, and finally curing at 300~310℃ for 0.5~1h.
[0032] The functions of each component in this invention are as follows: The polyimide resin or polyimide precursor described in this invention serves as a film-forming matrix to impart excellent heat resistance, film-forming properties, and adhesion stability to the coating. The graphite powder, as a solid lubricating phase, forms a low-shear lubrication interface due to its layered structure, thereby reducing frictional resistance and improving the friction-reducing and wear-resistant properties of the coating. The KH550 silane coupling agent and dispersant are used to improve the dispersion uniformity and interfacial compatibility of graphite in the polyimide system, so as to further improve the density and service stability of the coating.
[0033] To achieve stable adhesion and uniform spraying of the composite lubricating coating on the complex thread surface of fasteners, this invention employs a rotary spraying method to apply the composite lubricating coating to the fastener surface. During the spraying process, the fastener rotates around its own axis, and combined with multiple thin-spraying processes, the coating achieves uniform coverage on complex areas such as the thread crest, flank, and root. This effectively avoids problems such as local accumulation, root omissions, and uneven thickness that are prone to occur in conventional static spraying, thereby fully leveraging the friction-reducing, wear-resistant, and heat-resistant protective properties of the composite lubricating coating.
[0034] Example 1 Step 1: Preparation of composite slurry First, graphite powder is added to N,N-dimethylformamide and pre-dispersed by mechanical stirring / ultrasonic dispersion to obtain a graphite dispersion. Subsequently, polyimide resin or polyimide precursor is added to the graphite dispersion, followed by the addition of a dispersant. The mixture is then stirred and mixed to obtain a graphite / polyimide composite lubricating coating slurry. The dispersant is used to improve the dispersion uniformity and interfacial bonding state of graphite in the polyimide system.
[0035] Step 2: Preparation of intermediate layer slurry Deionized water, anhydrous ethanol, and KH550 silane coupling agent were mixed evenly in a volume ratio of 1:3:1 and placed in a water bath at 50°C for 1 h to obtain the intermediate layer slurry. Step 3: Matrix Pretreatment The substrate of fastener sample 2 was degreased, cleaned, and dried to remove surface contaminants; Step 4: Rotary spraying Place the fastener sample 2 on the rotary spraying table 3, and use the pneumatic spray gun 1 to spray the intermediate layer slurry onto the surface of the fastener sample 2 after step 3. The fastener sample 2 rotates around its own axis during the spraying process to improve the uniformity of the intermediate layer coverage in the threaded area, cylindrical surface and transition area.
[0036] Step 5: Pre-baking After the intermediate layer slurry is sprayed, the fasteners are pre-baked at 60℃~80℃ for 5min~20min to remove some of the solvent and to initially stabilize the coating.
[0037] Step 6: Multiple thin-spray composite coating The graphite / polyimide composite slurry obtained in step 1 is sprayed onto the surface of the fastener treated in step 5. During the spraying process, the fastener rotates around its own axis. After spraying, it is pre-baked. The spraying and pre-baking operations are repeated 2 to 4 times. The composite lubricating coating is deposited layer by layer by multiple thin sprays to reduce the risk of local sagging and thick coating accumulation.
[0038] Step 7: Heat treatment and curing The fasteners are heat-treated and cured in a stepwise manner to cure the polyimide resin or to induce an imidization reaction in the polyimide precursor, ultimately forming a graphite / polyimide composite lubricating coating on the fastener surface.
[0039] like Figure 2 The figure shows the coefficient of friction of the graphite / polyimide composite lubricating coating prepared in this embodiment at 350°C.
[0040] The above description is only the best specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the protection scope of the present invention.
[0041] The contents not described in detail in this specification are common knowledge to those skilled in the art.
Claims
1. A method for preparing a graphite-polyimide composite coating for titanium alloy fasteners, characterized in that: Includes the following steps: (1) Mix and disperse graphite powder with diluent to obtain graphite dispersion; (2) Add polyimide resin or polyimide precursor to graphite dispersion, then add dispersant, and stir to mix to obtain graphite / polyimide composite lubricating coating slurry; (3) Mix and stir deionized water, anhydrous ethanol and silane coupling agent to obtain intermediate layer slurry; (4) Apply the intermediate layer slurry to the surface of the fastener and pre-bake it; (5) Coat the graphite / polyimide composite lubricating coating slurry obtained in step (2) and cure it to obtain the graphite-polyimide composite coating.
2. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: In step (3), the volume ratio of deionized water, anhydrous ethanol and silane coupling agent is 1:2.5:1 to 1:3:
1. Stirring is carried out under water bath heating conditions, with a heating temperature of 48 to 52°C and a time of 1 to 1.2 hours.
3. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: In step (4), before coating, the fasteners are degreased, cleaned, and dried to remove surface contaminants.
4. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: In step (4), the pre-baking temperature is 60℃~80℃ and the time is 5min~20min.
5. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: In step (5), the graphite / polyimide composite lubricating coating slurry is applied by spraying. After spraying, it is pre-baked. The spraying and pre-baking are repeated 2 to 4 times to complete the coating.
6. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 5, characterized in that: A rotary spraying method is used, in which the fastener rotates around its own axis during the spraying process.
7. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: In step (5), the curing method is step curing, specifically as follows: first, cure at 140~145℃ for 0.5~1h, then cure at 200~210℃ for 0.5~1h, and finally cure at 300~310℃ for 0.5~1h.
8. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: The diluent is N-N dimethylformamide, and the volume ratio of N-N dimethylformamide to polyimide resin or polyimide precursor is 1:1 to 1:1.
1.
9. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: The mass of the polyimide resin or polyimide precursor is 65wt% to 75wt% of the total mass of the graphite polyimide composite coating, and the mass of the graphite powder is 25wt% to 35wt% of the total mass of the graphite polyimide composite coating.
10. The method for preparing a graphite-polyimide composite coating for titanium alloy fasteners according to claim 1, characterized in that: The dispersant is polyvinylpyrrolidone, and the mass of the dispersant is 5% to 10% of the mass of the graphite powder. The graphite powder is flake graphite with a particle size ≤11μm.
11. A graphite-polyimide composite coating for titanium alloy fasteners, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 10.